“PANCCult" extension project: Cultivating knowledge and flavors of Non-Conventional Food Plants” as a teaching-learning tool about biodiversity and its sustainable use in food - Sgrancio Uliana, Daniel; Marcia Passos Leal, Rhaiza; Jarske Gering, Sara; Aguiar Moraes, Érica; Freitas Brilhante de São José, Jackline (Guará Journal, 2025)
Unconventional Edible Plants (UNEPs) are plants or parts thereof that have the potential for use in human nutrition. Their inclusion in the diet can help revive food culture, promote cultural diversification, enable more sustainable food production, and improve eating habits. The objective of this work was to report on the experiences of the extension project "UNEPs: Cultivating Knowledge and Flavors of Unconventional Edible Plants" as a teaching-learning tool, exploring the biodiversity and sustainable use of these plants in food. This is an experience report of the activities carried out by the extension project from November 2021 to January 2024. The extension team developed outreach activities via social media; organized, participated in, and led events where information related to nutritional composition and culinary recipes was shared; carried out activities in an urban community garden; and produced scientific material on UNEPs and urban community gardens. It is concluded that the PANCCult extension project provided contributions in the dissemination of knowledge about PANC and provided opportunities for extension students, contributing to professional training, as well as encouraging the use of plant biodiversity in a sustainable manner.
Keywords: Food and Nutrition Security; Biodiversity; Sustainability; Health Education; Environmental Education